2003
DOI: 10.1161/01.hyp.0000084060.54314.f5
|View full text |Cite
|
Sign up to set email alerts
|

Na + /Ca 2+ Exchanger

Abstract: The Na+/Ca2+ exchanger regulates intracellular calcium ([Ca2+]i), and attenuation of Na+/Ca2+ exchange by oxidative stress might lead to dysregulation of [Ca2+]i. We have shown that the Na+/Ca2+ exchanger differs functionally and at the amino acid level between salt-sensitive and salt-resistant rats. Therefore, the purpose of these studies was to determine how oxidative stress affects the activities of the 2 Na+/Ca2+ exchangers that we cloned from mesangial cells of salt-resistant (RNCX) and salt-sensitive (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…NCX1.2 and NCX1.3 were described to be functional in a mouse DCT cell line; however, NCX1.7 was not expressed [14] . In another study, NCX1.3 and NCX1.7 were compared, demonstrating a difference in buffer capacity and oxidative stress response [35,36] . However, this was later partly explained by the used NCX construct, which contained a difference of one residue at position 218, which is not present in the splice region [37] .…”
Section: Discussionmentioning
confidence: 99%
“…NCX1.2 and NCX1.3 were described to be functional in a mouse DCT cell line; however, NCX1.7 was not expressed [14] . In another study, NCX1.3 and NCX1.7 were compared, demonstrating a difference in buffer capacity and oxidative stress response [35,36] . However, this was later partly explained by the used NCX construct, which contained a difference of one residue at position 218, which is not present in the splice region [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, peroxynitrite inhibition of Na ϩ /Ca 2ϩ exchange activity has been reported in an in vitro preparation of microsomes from smooth muscle pulmonary artery (26) and in that of salt-sensitive hypertensive rats (50), but the sites of action were not established.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, arteries from smooth muscle-specific NCX1 knockout (NCX1 smϪ/Ϫ ) mice exhibit reduced Ca 2ϩ entry into vascular smooth muscle cells and reduced myogenic tone (25,35). Renovascular function plays a pivotal role in salt-dependent hypertension (9,34), and it has been reported that Na ϩ /Ca 2ϩ exchanger mechanisms are disrupted in saltsensitive hypertension (2,21,32). In contrast, other groups observed enhanced expression of NCX1 in arterial smooth muscle in several forms of hypertension (10,23,39).…”
mentioning
confidence: 99%